The The Effectiveness of Integrated Scientific Literacy Student Worksheets for the Use of Physics Practical Kits on Temperature and Heat Materials on the Learning Outcomes of Grade XI Senior High School Students - Firdaus, Aulia (Department of Physics Universitas Negeri Padang, 2025)
The Independent Curriculum (Curriculum Merdeka) is a curriculum that allows all educational units the freedom to utilize various teaching tools to improve learning outcomes. However, student learning outcomes at SMAN 2 Lubuk Sikaping are still relatively low. A possible solution to improve student learning outcomes is to use integrated scientific literacy worksheets (LKPD). The purpose of this study was to determine the effectiveness of scientific literacy worksheets on the learning outcomes of grade XI students in Phase F at SMAN 2 Lubuk Sikaping. This study used a quasi-experimental design. It employed a posttest-only control group design. The population was all grade XI students in Phase F at SMAN 2 Lubuk Sikaping. The sampling technique used was cluster random sampling. The sample size for this study was grades XI and X in Phase E7. The experimental class used a physics worksheet containing scientific literacy, while the control class used the school-provided worksheets. The research results show that the implementation of student worksheets (LKPD) containing scientific literacy significantly improves student learning outcomes, both in terms of knowledge and skills. This is evidenced by the results of the hypothesis test or t-test conducted on student learning outcomes in two aspects: knowledge and skills. The results obtained were t-test > t-table, thus confirming and rejecting